2015
DOI: 10.1080/19371918.2015.1046628
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude about HIV/AIDS among HIV-Positive Individuals in Davangere

Abstract: A cross-sectional study was carried out on 100 HIV patients (55 male and 45 female) age 21 years and older registered at the Antiretroviral Therapy Centre of Chigateri General Hospital, Davangere, Karnataka, India, to evaluate their knowledge and attitude toward HIV. Overall, the source of knowledge about AIDS was through newspaper or television, 38% were aware of their AIDS status, 61% disclosed their status to family, 86% had incorrect knowledge about transmission, 57% experienced no moral support, 62% felt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The sample sizes ranged from 36 23 to 132 678. 52 The primary target population across studies were students (n=19), 10 , 14 , 15 , 17 , 21 , 23 , 26 , 27 , 29 , 31 , 34 , 35 , 37 , 38 , 40 , 42 , 46 , 47 , 49 general population (n=9), 9 , 13 , 18 - 20 , 43 , 48 , 51 , 52 healthcare workers [HCWs] (n=5), 8 , 24 , 28 , 41 , 50 people living with HIV (PLWHIV) (n=4), 25 , 32 , 33 , 36 and female sex workers (FSWs) (n=3). 11 , 12 , 45 More details are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes ranged from 36 23 to 132 678. 52 The primary target population across studies were students (n=19), 10 , 14 , 15 , 17 , 21 , 23 , 26 , 27 , 29 , 31 , 34 , 35 , 37 , 38 , 40 , 42 , 46 , 47 , 49 general population (n=9), 9 , 13 , 18 - 20 , 43 , 48 , 51 , 52 healthcare workers [HCWs] (n=5), 8 , 24 , 28 , 41 , 50 people living with HIV (PLWHIV) (n=4), 25 , 32 , 33 , 36 and female sex workers (FSWs) (n=3). 11 , 12 , 45 More details are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The subgroup analysis showed the level of knowledge about HIV/AIDS was high among FSWs (89%), 11 , 12 , 45 while the level of knowledge among PLWHIV was 65%. 25 , 32 , 33 , 36 Additional information is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Stigma also continues to act as a common barrier to timely care-seeking, treatment, and prevention in India (36, 41, 42), though studies have shown mixed results in terms of stigma’s relationship to ART adherence once on treatment (43, 44). While disclosure varies among studies, the main reasons given for non-disclosure were shame and fear of discrimination and isolation (36, 4547). Within the health care setting, PLWH in India have reported experiences of provider discrimination, purposeful delay or even denial of treatment (47), and breach of confidentiality following their diagnosis (48).…”
Section: Introductionmentioning
confidence: 99%
“…While disclosure varies among studies, the main reasons given for non-disclosure were shame and fear of discrimination and isolation (36, 4547). Within the health care setting, PLWH in India have reported experiences of provider discrimination, purposeful delay or even denial of treatment (47), and breach of confidentiality following their diagnosis (48). These PLWH-reported experiences of provider stigma appear to be validated in our previous work examining stigma among Indian health care workers (3, 7)…”
Section: Introductionmentioning
confidence: 99%
“…Many of our interviewees (64%) had known their HIV status for more than a year but refused to reveal this information to intimate friends or family members. This refusal to communicate their medical condition can most probably be explained by the fear of being stigmatized by the society and the loss of esteem of the entourage [17-20]. Indeed, in much of the existing literature on stigma, investigators do not provide its definition at all, or refer to ‘a mark of disgrace’, or some similar aspect, such as stereotyping or social rejection.…”
Section: Discussionmentioning
confidence: 99%